The effect of self-efficacy and assertive on students' business negotiation and communication skills in vocational high schools (VHS) - Sriyanto, Sriyanto (EBSCO Industries, Inc., 2022)
Communication and negotiation provide significant contribution to the success and achievement of an organization. This study aims to examine factors influencing students' negotiation and communication in the Online Business and Marketing Department of VHS. The data used a questionnaire of 426 respondents consisting of VHS students throughout Central Java, then processed using inferential statistical analysis with WARP PLS-SEM. The researchers obtain several findings, that is self-efficacy and assertive variables do not have significant contribution to the business communication variable. In contrast, self-efficacy and assertive variables have significant contribution to the negotiation variable. Similarly, both variables found have no indirect effect on the business communication variable. Eventually, this study finds that students' communication skills during their study go hand in hand with knowledge and attitudes.